Polarization selective tunable filter via tuning of Fano resonances in MEMS switchable metamaterials - Teng, Jing Hua (2013)
We experimentally demonstrated polarization selective tuning of Fano resonance in switchable metamaterials based on Microelectromechanical systems (MEMS). The transmission spectra of TE polarized incidence can be tuned while maintain those of the TM polarized incidence by continuously shifting one trapezoid of the cross-shaped unit cell. It measures a Fano resonance frequency shift of 37.9% (low frequency region) and 25.7% (high frequency region) for TE polarized incidence and only 0.8% for TM polarized incidence. Compared with the previous efforts on tunable metamaterials, the switchable metamaterials promises unprecedented tunability, such as single to dual band tuning, polarization selective tuning.